The Concept of Baligh Perspective of Fiqh and Positive Law - Amin, Ibnu; Lendrawati, Lendrawati; Efendi, Faisal; Hertasmaldi, Hertasmaldi (Institut Agama Islam Negeri Curup, 2022)
This paper aims to elaborate the concept of baliqh from the perspective of fiqh and Positive Law in Indonesia as the fuqaha's opinion about baligh and adult in Law no. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage, Law No. 24 of 2013 concerning Population Administration and Law No. 35 of 2014 concerning Child Protection. The research method used is a literature study by tracking, comparing and analyzing doctrinal normative law through a qualitative approach in content analysis about baligh and adulthood. The results of the research revealed that baligh in fiqh with the rusyd benchmark when referring to the signs of puberty, namely ihtilam (wet dreams for men), menstruation (for women), hair growth around the pubic and age ranges from 15 to 19 years. Whereas, in the Indonesian Positive Law, adults are classified based on interests, namely adults for marriage age limit of 19 years for men and women, adults to have population administration (KTP), driver's license and have political rights at the age of 17 years. To determine the limit of children, notary position and citizenship age 18 years while income tax, free from guardianship and recognized as labor at the age of 21 years. The determination of the limits of puberty and adulthood is included in the category of mashlahah 'ammah, namely the general benefit that concerns the interests of many people.